Lebanese teachers' perceptions of digital citizenship and professional development needs for effective digital citizenship education - Fatin Sleem; Samira Nicolas (Social Sciences and Humanities Open)
This study contributes to the limited research on digital citizenship (DC) in Lebanon by examining demographic influences and perceived impact of digital citizenship education (DCE) training workshops. Specifically, this study explores Lebanese middle school teachers’ perceptions of DC and is the first study to assess the impact of DCE training in Lebanon. Data was collected through a teacher questionnaire based on the Digital Citizenship Scale by Kus et al. (2017). The participants were 214 middle school teachers in Lebanon and the data was analyzed using descriptive statistics and one-way ANOVA. The findings reveal that teachers' overall perceptions of DC are characterized by a mix of awareness and uncertainty. While teachers demonstrated high awareness of digital ethics, skills, and trade, they exhibited lower confidence in digital communication and uncertain perceptions of digital rights, responsibilities, participation, security, and critical thinking. The results indicate no significant variations in teachers' overall perceptions of DC by age, except for the element of digital skills. Educational attainment was positively correlated with perceptions of digital communication and skills, with higher-educated teachers displaying more favorable views. Teaching experience had no significant influence on overall DC perceptions, except for digital skills. Notably, participation in DCE training workshops did not significantly impact teachers' perceptions of DC or its elements. This study highlights the need for tailored professional development programs, enhanced curriculum integration, and equitable access to technology to address gaps in DC perceptions among Lebanese teachers. These measures are critical for fostering the effective implementation of DCE in Lebanese schools.